Pelatihan Penyelenggaraan Tajhîzul Mayit pada Siswa SMP Annur Bululawang Malang - Bisri, Agung Muhamad; Husni, Muhammad (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This community service program was initiated in response to the limited direct involvement of students in the practice of tajhîz al-mayyit (Islamic funeral management), despite the fact that its fundamental concepts had been introduced in Islamic Religious Education classes. The main issue identified was the lack of hands-on experience, which caused students’ understanding to remain predominantly theoretical and insufficiently structured. Therefore, this activity aimed to reinforce correct comprehension while simultaneously equipping students with practical skills in accordance with Islamic teachings, particularly in the procedures of bathing, shrouding, performing the funeral prayer, and burying the deceased. The implementation of the program involved interactive material delivery, demonstrations using mannequins, group-based practice simulations, as well as reflective and evaluative discussions. The activity was attended by all eighth- and ninth-grade students of SMP Annur Bululawang, Malang, who participated with a high level of enthusiasm. The results revealed a clear improvement in students’ understanding of the stages of tajhîz al-mayyit, more organized and accurate practical execution, and increased confidence and mental readiness in dealing with death-related situations in their surrounding environment. In addition, students demonstrated enhanced empathy and a stronger sense of both religious and social responsibility. It can therefore be concluded that this training program was effective in developing students’ practical religious competence and is suitable to be implemented as a regular school program.